Nanopore sequencing of protozoa: Decoding biological information on a string of biochemical molecules into human-readable signals - Branden Hunter; Timothy Cromwell; Hyunjin Shim (Computational and Structural Biotechnology Journal)
Biological information is encoded in a sequence of biochemical molecules such as nucleic acids and amino acids, and nanopore sequencing is a long-read sequencing technology capable of directly decoding these molecules into human-readable signals. The long reads from nanopore sequencing offer the advantage of obtaining contiguous information, which is particularly beneficial for decoding complex or repetitive regions in a genome. In this study, we investigated the efficacy of nanopore sequencing in decoding biological information from distinctive genomes in metagenomic samples, which pose significant challenges for traditional short-read sequencing technologies. Specifically, we sequenced blood and fecal samples from mice infected with Trypanosoma brucei, a unicellular protozoan known for its hypervariable and dynamic regions that help it evade host immunity. Such characteristics are also prevalent in other host-dependent parasites, such as bacteriophages. The taxonomic classification results showed a high proportion of nanopore reads identified as T. brucei in the infected blood samples, with no significant identification in the control blood samples and fecal samples. Furthermore, metagenomic de novo assembly of these nanopore reads yielded contigs that mapped to the reference genome of T. brucei in the infected blood samples with over 96 % accuracy. This exploratory work demonstrates the potential of nanopore sequencing for the challenging task of classifying and assembling hypervariable and dynamic genomes from metagenomic samples.